CLINICAL AND EPIDEMIOLOGICAL FEATURES OF MODERN COURSE OF SHIGELLOSIS IN ADULTS - Majidova , Shahrizoda; Abdukaxarova , Muattar (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article presents a clinical and epidemiological analysis of shigellosis and its share among bacterial intestinal infections. Most cases were observed in adults aged 25–50 years. A seasonal pattern typical for intestinal infections (summer–autumn) persisted, but the specific seasonality of shigellosis seen in the past was absent. The main transmission factors were dairy products and water. Shigella flexneri was the most common causative agent, often causing moderate to severe colitic forms with fever, crampy abdominal pain, scarce stools with mucus, and usually no tenesmus.